UNDERSTANDING MODEL BY DESIGN FOR ELEMENTARY SCHOOL STUDENTS' DEEP UNDERSTANDING - Suriswo; Hastin Budisiwi; Yovian Yustiko Prasetya (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to analyze the implementation of the Understanding by Design (UbD) model in improving the in-depth understanding of fifth-grade students in four elementary schools. Using a qualitative approach with a case study design, the study was conducted for six months (January-June 2025) at Slawi Wetan 03 Elementary School, Slawi Wetan 05 Elementary School, Kagok 01 Elementary School, and Procot Elementary School. Data were collected through participant observation, in-depth interviews with eight classroom teachers, lesson plan documentation, student assignments, and authentic project analysis. The results showed that the implementation of UbD significantly improved the quality of teachers' lesson plans, particularly in formulating learning objectives and designing authentic assessments. Students demonstrated improved ability to connect concepts, think critically, and apply knowledge in real contexts. Classroom interactions became more active and learning motivation increased. The main challenges were teacher workload and limited infrastructure. The study concluded that UbD is effective as a meaningful learning model in elementary schools, in line with the spirit of the Independent Curriculum. Research recommendations include ongoing training and the development of local UbD modules